EPR study of the structural phase transitions in Fe3+ doped TlInS2 - Mikailov, F. A.; Kazan, S.; Rameev, B. Z.; Acikgoz, M.; Aktas, B. (Wiley-V C H Verlag Gmbh, 2006)
The results of low temperature EPR investigations of Fe doped TlInS2 single crystals in the temperature range 5-300 K are presented. The EPR signal due to Fe3+ centers located at the centers of InS4 tetrahedrons has been observed. It has been established that the resonance lines exhibit a slight shift and remarkable splitting at the temperatures lower than 200 K, which is attributed to the effect of the ferroelectric phase transition. The rotational patterns of the resonance fields reveal a doubling of the number of centers at low temperatures. The preliminary simulation indicates that the doubling is related to the rotation of the principal axis system of the centers, while the magnitude of fine structure splitting is nearly the same. (c) 2006 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
International Conference on Nanoscale Magnetism (ICNM 2005) -- JUL 03-07, 2005 -- Gebze, TURKEY
Keywords: Incommensurate Phase; Crystal